Innovative approaches to enhancing maternal and newborn survival: Indonesia's experience in an era of global commitments to reducing mortality. (27th February 2019) - Agarwal, Koki; Lilly, Katherine; Smith, Jeffrey
Abstract: Globally, countries have made impressive strides toward achieving targets set by the Millennium Development Goals (MDGs) to reduce maternal mortality. The subsequent Sustainable Development Goals (SDGs) have further challenged countries to accelerate these reductions. While Indonesia invested in several initiatives to improve care for mothers and newborns and made large gains in improving skilled care at birth, the country fell short of its MDG target. This paper outlines some of the remaining challenges and highlights the role of the US Agency for International Development‐funded Expanding Maternal and Neonatal Survival (EMAS) program in eliminating the barriers to improved care. Achieving the SDGs by 2030 will require strong cross‐sectoral collaboration and innovative approaches, such as the recent launch of Indonesia's national health insurance program, which can accelerate reductions in mortality by reaching women most in need of services. Abstract : This paper describes the challenges Indonesia faces in reducing maternal and neonatal mortality and highlights key approaches to catalyze reduction in mortality.